Consumer Perceptions Of Service Quality And Prices Of MSMEs Delivery Services - Athar, Handry Sudiartha; Faerrosa, Lady; Sutanto, Himawan (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
Consumer perception is very important for business. This study aims to explore consumer perceptions of service quality and prices for MSMEs delivery services. Ten informants in this study are consumers who have used the services. The data analysis carried out is by reducing the results of interviews that are considered relevant, displaying data in the form of data groups that show the dimensions of perception, and drawing conclusions after careful analysis. The results show that consumer perceptions of the quality of MSMEs delivery services are mostly positive. However, in terms of responsiveness, the response time is currently still considered too slow so that it often causes consumer dissatisfaction. This is certainly seen as a weakness for MSMEs and needs to be solved in order to stay in business. This study also found that the use of uniforms by MSME delivery services is also important for consumers. Thus, this can begin to be made a priority by MSMEs to build a positive consumer perception of MSMEs. Meanwhile, the perception of consumers towards the price set by MSMEs is in accordance with consumer purchasing power and the quality of services. Therefore, it is concluded that it is in accordance with the Islamic economy. The results can be used as a reference by MSMEs and large-scale businesses, not only at the location of this study, but also in other regions in evaluating business strategies and developing innovative delivery services that suit consumer needs.